Short and long term outcomes of laparoscopic fenestrating or reconstituting subtotal cholecystectomy versus laparoscopic total cholecystectomy in the management of acute cholecystitis. Issue 5 (May 2022) - Loh, Alex Y.H.; Chean, Chung Shen; Durkin, Damien; Bhatt, Anand; Athwal, Tejinderjit S.
Abstract: Background: Strasberg proposed classifying subtotal cholecystectomy techniques into fenestrating (fSC) and reconstituting (rSC) subtypes. The aim of this study is to compare our outcomes of laparoscopic subtotal cholecystectomies of both subtypes against laparoscopic total cholecystectomy (TC) in difficult emergency laparoscopic cholecystectomies. Methods: Patients undergoing emergency laparoscopic cholecystectomy were identified over 2 years and all Nassar scale 3 and 4 cholecystectomies were included for analysis. Results: 108 fSC and 24 rSC were compared against 317 TC. Patients undergoing fSC and rSC were older and more likely to be male. fSC (128 min) and rSC (141 min) recorded longer median operative times than TC (109). Post-operative ERCP was more common after rSC (16.7%). Patients undergoing fSC (2 days) and rSC (3.5 days) had longer post-operative stays. Bile leaks were more likely in fSC (9.3%) and rSC (8.3%) compared to TC (1.9%), Long term morbidity was higher in the rSC group (12.5% vs 10%). And these were solely due to gallbladder remnant complications. Conclusion: Laparoscopic fSC and rSC techniques are associated with a higher rate of bile leaks and rSC has more long term morbidty as compared to TC.